2008
DOI: 10.1364/oe.16.003859
|View full text |Cite
|
Sign up to set email alerts
|

Switching of polymer-stabilized vertical alignment liquid crystal cell

Abstract: This work investigates the switching characteristics of the polymer-stabilized vertical alignment (VA) liquid crystal (LC) cell. The experimental results reveal that the fall time of the cell declines as the monomer concentration increases because the vertically-aligned polymer networks accelerate the relaxation of the LC molecules. Furthermore, the formed polymer networks impede the growth and annihilation of LC defects, suppressing the optical bounce in the time dependent transmittance curve of the cell when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…The doped LC cell had a faster rise time than the VA LC cell because cyclic dimers of the carboxylic acid group formed between the gelator molecules dispersed in the LC bulk [ 32 ]. The aggregated gelators functioned as the polymer sticks in polymer-stabilized LC (PSLC) cells [ 37 , 38 , 39 ], suppressing the optical bounce and improving the rise time of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…The doped LC cell had a faster rise time than the VA LC cell because cyclic dimers of the carboxylic acid group formed between the gelator molecules dispersed in the LC bulk [ 32 ]. The aggregated gelators functioned as the polymer sticks in polymer-stabilized LC (PSLC) cells [ 37 , 38 , 39 ], suppressing the optical bounce and improving the rise time of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the response time of this DFLC-based hybrid system at the applied voltage of 16 V. The measured rising time and falling time are~60 ms and~270 ms, respectively. Huang et al [54] have reported that the rising time τ on and falling time τ off of the DFLC- based device driven by relatively high voltages can be written as t on ¼ g 1 d 2 " 0 Δ" j jV 2 À k eff p 2 ð Þ ffi g 1 " 0 Δ" j jE 2 ð Þ and…”
Section: Resultsmentioning
confidence: 99%
“…The temperature dependence of the bend elastic constant (K 33 ) of Compounds 1-10 are shown in Figure 3 The K 33 values in the nematic phase for Compounds 9 and 10 are around 7 pN and 8 pN, [34] respectively, and are found to increase quite steeply, especially as the N-SmB phase transition is approached (Figure 3(b)). Out of the three positive dielectric anisotropic compounds (11)(12)(13) only Compound 11 shows threshold behaviour in planar aligned cell. The Fréedericksz voltage was used to determine temperature dependence of the splay elastic constant.…”
Section: Bend Elastic Constant Measurementsmentioning
confidence: 99%
“…Of the existing technologies, the VA mode is one of the best approaches that are currently being used in LCDs, due to their superior picture quality with wide viewing angle, [8,9] high contrast [10] and video-compatible switching times [11][12][13][14] over the conventional twisted nematic (TN) [15][16][17][18] or the more recent in-plane switching (IPS) [19][20][21][22][23][24][25][26][27] mode LCDs. The important properties of liquid crystalline materials required for electro-optical devices working in the VA mode are a nematic phase with a relatively broad temperature range (−40°C to 110°C), low to moderate birefringence (Δn~0.1-0.2), large negative dielectric anisotropy (Δε~−5), low bend elastic constant (K 33 8-10 pN), low rotational viscosity (γ 1 < 100 mPas), high thermostability and photochemical stability.…”
Section: Introductionmentioning
confidence: 99%